JUNIOR HIGH SCHOOL STUDENTS’ SELF-REGULATED LEARNING - Nitiasih, PK; Mahayanti, NWS; Wijayanti, NPR (International Journal of Language and Literature, 2018)
In this globalisation era, being able to manage our own learning is a mist and self-regulated learning can be the answer for making the students be able to do so. Identifying self-regulated learning implemented by the students of Junior High School in Buleleng sub-district and also identifying self-regulated aspects which were mostly implemented by Junior High School students in Buleleng sub-districtwerethepurposesofthis study. A total of 444 students from JuniorHighSchoolswhichhaveimplementedcurriculum 2013 were taken as the subjects of this study. Asaqualitativeresearch, the instruments used in this study were observation checklist, questionnaires and also interview guide. The result of the study shows that 78% of Junior High School students in Buleleng sub-district haveimplemented self-regulated learning and there aretwo aspects of self-regulated learning which aremostly implemented by the students, theyareself-judgment and self-reaction in which those two aspects are in self-reflection phase.